Rhinovirus 3C protease suppresses apoptosis and triggers caspase-independent cell death - Lötzerich, Mark (Cell Death Dis, 2018)
Apoptosis and programmed necrosis (necroptosis) determine cell fate, and antagonize infection. Execution of these complementary death pathways involves the formation of receptor-interacting protein kinase 1 (RIPK1) containing complexes. RIPK1 binds to adaptor proteins, such as TRIF (Toll-IL-1 receptor-domain-containing-adaptor-inducing interferon-beta factor), FADD (Fas-associated-protein with death domain), NEMO (NF-κB regulatory subunit IKKγ), SQSTM1 (sequestosome 1/p62), or RIPK3 (receptor-interacting protein kinase 3), which are involved in RNA sensing, NF-κB signaling, autophagosome formation, apoptosis, and necroptosis. We report that a range of rhinoviruses impair apoptosis and necroptosis in epithelial cells late in infection. Unlike the double-strand (ds) RNA mimetic poly I:C (polyinosinic:polycytidylic acid), the exposure of dsRNA to toll-like receptor 3 (TLR3) in rhinovirus-infected cells did not lead to apoptosis execution. Accordingly, necroptosis and the production of ROS (reactive oxygen species) were not observed late in infection, when RIPK3 was absent. Instead, a virus-induced alternative necrotic cell death pathway proceeded, which led to membrane rupture, indicated by propidium iodide staining. The impairment of dsRNA-induced apoptosis late in infection was controlled by the viral 3C-protease (3Cpro), which disrupted RIPK1-TRIF/FADD /SQSTM1 immune-complexes. 3Cpro and 3C precursors were found to coimmuno-precipitate with RIPK1, cleaving the RIPK1 death-domain, and generating N-terminal RIPK1 fragments. The depletion of RIPK1 or chemical inhibition of its kinase at the N-terminus did not interfere with virus progeny formation or cell fate. The data show that rhinoviruses suppress apoptosis and necroptosis, and release progeny by an alternative cell death pathway, which is controlled by viral proteases modifying innate immune complexes.